2020
DOI: 10.2147/hmer.s243277
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hepatic Differentiation of Marmoset Embryonic Stem Cells and Functional Characterization of ESC-Derived Hepatocyte-Like Cells</p>

Abstract: Background: Primary human hepatocytes (PHHs) are the ideal candidates for studying critical liver functions such as drug metabolism and toxicity. However, as they are isolated from discarded livers that are unsuitable for transplantation, they possess limited expansion ability in vitro and their enzymatic functions deteriorate rapidly because they are often of poor quality. Therefore, there is a compelling reason to find reliable alternative sources of hepatocytes. Methods: In this study, we report on efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Recently, Aravalli et al have carried out efficient hepatic differentiation of marmoset embryonic stem cells (ESCs) into functional hepatocyte-like cells (HLC) and demonstrated that the generated HLCs possessed specific characteristics similar to those of primary human hepatocytes. HLCs might be an optimal model for research in cell therapy of human liver diseases including hepatotropic virus infections, while the expression of CYP genes involved in the breakdown of various toxic molecules and chemicals also makes HLCs suitable for research of drug metabolism [ 95 ]. The potential for neural differentiation has been reported by Shimada et al [ 96 ].…”
Section: Common Marmoset Embryonic Stem Cellsmentioning
confidence: 99%
“…Recently, Aravalli et al have carried out efficient hepatic differentiation of marmoset embryonic stem cells (ESCs) into functional hepatocyte-like cells (HLC) and demonstrated that the generated HLCs possessed specific characteristics similar to those of primary human hepatocytes. HLCs might be an optimal model for research in cell therapy of human liver diseases including hepatotropic virus infections, while the expression of CYP genes involved in the breakdown of various toxic molecules and chemicals also makes HLCs suitable for research of drug metabolism [ 95 ]. The potential for neural differentiation has been reported by Shimada et al [ 96 ].…”
Section: Common Marmoset Embryonic Stem Cellsmentioning
confidence: 99%
“…Moreover, they can be converted from the primed to a naive-like state using transgenes to increase their pluripotency in vitro [ 47 ]. cjESCs were recently differentiated into highly functional hepatocyte-like cells (cjESC-HLCs) [ 48 ], which would be valuable for in vitro studies on infectious diseases, regenerative medicine and drug metabolism. While it has been shown that iPSCs can allograft into the putamen of cynomolgus monkeys without immunosuppression [ 49 ], cjESC-derived cells were only tested using immunosuppressive agents such as tacrolimus [ 50 ].…”
Section: Marmoset Embryonic Stem Cellsmentioning
confidence: 99%
“…To overcome these bottlenecks, successful attempts have been made to model HCV infection in HLCs isolated from human-induced pluripotent stem cells (iPSCs) [ 84 , 85 ] and human ESCs [ 85 ]. Since C. jacchus is a good surrogate for HCV, the common marmoset could be an appropriate animal model to investigate hepatitis viruses in in vitro studies; and recently generated cjESC-HLCs [ 48 ] could be very valuable tools for in vitro experiments.…”
Section: Callithrix Jacchus Models Of Human LIVmentioning
confidence: 99%
See 2 more Smart Citations